The potential of carbon sequestration in community forests for climate change mitigation and disaster risk reduction - Aprilia, Rosa (ASEAN Natural Disaster Mitigation and Education Journal, 2025)
Background: Climate change is a significant global concern, with its effects observed worldwide. Community forest management, which involves local communities in managing and utilizing forest resources, is a sustainable approach to forest preservation. This method not only provides economic benefits but also contributes to carbon sequestration, a strategy for mitigating global warming. This research explores the role of community forests in carbon sequestration and climate change mitigation, focusing on Sidodadi Village in Lawang District, Malang Regency. Method: The research used a quantitative approach, applying the allometric method for carbon calculation. Findings: The community forest in Sidodadi Village showed notable carbon sequestration: 381.0334 tons C/ha for Jabon (Anthocephalus cadamba), 374.8768 tons C/ha for Balsa (Ochroma pyramidale), and 40.9963 tons C/ha for Sengon (Albizia chinensis). Conclusion: The findings highlight the substantial carbon storage potential of community forests and their contribution to environmental sustainability. Raising public awareness of the importance of preserving these forests is crucial, given their role in combating climate change. Novelty/Originality of this article: This study emphasizes the significant contribution of community forests to carbon sequestration and the potential role they play in climate change mitigation, offering valuable insights for environmental management strategies.